Anticipating the future of digital transformation in Algeria - LOUCIF, Amar (Journal of Human Sciences, 2025)
Digital transformation is one of the basic pillars in the management of the global economy, and it means obtaining information, processing it and transforming it into knowledge capable of creating added value. Through this article, we aim to anticipate the future of digital transformation in Algeria and the most important driving forces for it. We relied on the forward-looking analytical approach when studying future scenarios for digital transformation in Algeria, as the study concluded that Algeria’s performance in the field of digital transformation remains modest, and is dependent on both infrastructure. Digital, human capital, innovation, knowledge and technology, finance, digital security, and the Internet. The study recommends the need to establish an appropriate ground at the national level for digital transformation, whether it is related to the legal aspect, the human aspect and the material and financial capabilities.